NADPH oxidase inhibition rescues keratinocytes from elevated oxidative stress in a 2D atopic dermatitis and psoriasis model. Issue 8 (22nd July 2020) - Emmert, Hila; Fonfara, Melina; Rodriguez, Elke; Weidinger, Stephan
Abstract: Emerging evidence suggests oxidative stress plays a role in the pathophysiology of both atopic dermatitis (AD) and psoriasis (PSO). We established in vitro models of AD and PSO skin, and characterized these models in regard to their oxidative stress state. Both AD and PSO model keratinocytes exhibited elevated reactive oxygen species (ROS) levels and accumulated more DNA damage than control cells after oxidative stress induced by 250 µmol/L H2 O2 . Elevated ROS levels and DNA damage accumulation could be inhibited by the NADPH oxidase (NOX) inhibitor diphenyleneiodonium (DPI). Further, immunofluorescence analysis revealed the presence of both NOX1 and NOX4 in keratinocytes. By inhibiting NOX1, stress‐related signalling cascades and elevated ROS levels could be abrogated, and survival of AD and PSO cells improved. Taken together, this study reveals that inhibition of NOX inhibition could abrogate elevated oxidative stress in a 2D model of AD and PSO.